Heart Rate Variability: a Follow-up in Elite Soccer Players Throughout the Season - Naranjo, J.; De la Cruz, B.; Sarabia, E.; De Hoyo, M.; Domínguez-Cobo, S. (International Journal of Sports Medicine, 2015)
Heart rate variability (HRV) can provide useful information on physiological adaptations to training, but its role is unknown in professional soccer. The aim of this study was to determine an HRV profile in professional soccer over a season. A total of 504 records were made of the heart beat signal throughout a season from 22 professional soccer players. HRV was recorded in a sitting position, early morning and fasting for a period of 10 min. Standard deviation 1 and 2 (SD1, SD2), standard deviation of normal to normal R-R intervals (SDNN), Root Mean Square of the Successive Differences (rMSSD), percentage of RR intervals > 50 ms (pNN50), Sample Entropy (SampEn), Stress Score (SS) and sympathetic/parasympathetic ratio (S/PS ratio) were calculated. SDNN, rMSSD, pNN50, SD1 and SD2 showed an identical behaviour throughout the season, with lower values in the pre-season and the end of the season. SS and S/PS ratio indicated a sympathetic stress alert in the same periods. A weekly recording of the HRV over a 10 min period that includes a Poincaré plot with SS and S/PS ratio and at least one variable of the time domain is a useful tool for the follow-up of the individual assimilation of weekly workloads, including the game.
Keywords: heart rate variability; professional soccer player; stress score; sympathetic/parasympathetic ratio